International market selection and export performance: a transaction cost analysis. Issue 5 (9th May 2016) - He, Xinming; Lin, Zhibin; Wei, Yingqi
Abstract : Purpose: This paper aims to provide a transaction cost analysis (TCA) perspective to exporting firms' selection of foreign markets and the performance consequences of this international market selection (IMS) decision. This paper proposes a conceptual framework that hypothesizes the relationship between transaction cost factors, IMS and export performance. Design/methodology/approach: This paper tests the proposed framework with a database of Chinese manufacturing firms using regression models and controlling for possible endogeneity. The endogeneity issue may arise due to IMS being influenced by unobserved industrial/firm attributes. Findings: The results show that transaction cost factors are able to explain IMS. Furthermore, firms whose decisions have incorporated transaction cost factors perform significantly better than their rivals. Research limitations/implications: Understanding transaction costs helps decision-makers formulate more efficient IMS strategy to achieve superior export performance. Future research on IMS may examine "passive exporting", i.e. exporting initiated by overseas buyers, consider the role of institutional distance and use other approaches toward cultural distance-based IMS. Originality/value: This study adds a new theoretical underpinning for IMS by developing a framework based on TCA, and thus broadens the applications of TCA into IMS. Our empirical results support this extension.